Service Quality Analysis to Increase Customer Satisfaction at Zara Outlets in Capital City - Hansen Albertus Sutanto (Journal of Current Research In Multidisciplinary, 2024)
This research aims to analyze service quality to increase customer satisfaction. This research uses quantitative research methods. The sampling technique used is probability sampling. The number of samples in this research was 100. The research used the Importance Performance Analysis (IPA) measurement model. Based on the research results, it can be concluded that the reliability and responsiveness indicators of employees are considered ideal because their performance values exceed consumer expectations. This shows that employees can be relied on to provide service and are responsive to consumer needs. However, assurance indicators still need to be improved because there are performance values that are still low compared to consumer expectations. Efforts to improve this indicator can be made by increasing employees' knowledge and confidence in the products or services offered. On the other hand, the empathy indicator is considered ideal because its performance value also exceeds consumer expectations. This shows that employees are able to provide service with empathy and understand consumer needs well. Tangible indicators also need to be improved because there are performance values that are still below consumer expectations. Improvements in this indicator can be made by improving the physical quality of the products or facilities offered to consumers. Therefore, efforts are needed to improve the assurance and tangible indicators so that they can meet consumer expectations as a whole. In this way, the overall quality of service can be improved to increase customer satisfaction.